A translation by 3 units to the right.
Answer:
3.2 x 10^13
Step-by-step explanation:
(8x10^4)(4x10^8)
reorder the terms using the commutative property
(8x4)x(10^4x10^8)
multiply
32x (10^4 x 10^8)
= 32 x 10^4+8
= 32 x 10^12
now convert to scientific notation
=3.2 x 10^13
Wouldn't the ratio from length to width be 8?
Answer:
y = -3x +4
Step-by-step explanation:
Using the expression for y, we can substitute that into the second equation:
... x + (1/3)(-3x +4) = 4/3
... 4/3 = 4/3 . . . . . simplify (True for any value of x.)
<em>These equations are dependent and have an infinite number of solutions</em>.